Design, Bioanalytical, and Biomedical Applications of Aptamer-Based Hydrogels - Di, Ya; Wang, Ping; Li, Chunyan; Xu, Shufeng; Tian, Qi; Wu, Tong; Tian, Yaling; Gao, Liming (Frontiers in Medicine, 2020)
Aptamers are special types of single-stranded DNA generated by a process called systematic evolution of ligands by exponential enrichment (SELEX). Due to significant advances in the chemical synthesis and biotechnological production, aptamers have gained considerable attention as versatile building blocks for the next generation of soft materials. Hydrogels are high water-retainable materials with a three-dimensional (3D) polymeric network. Aptamers, as a vital element, have greatly expanded the applications of hydrogels. Due to their biocompatibility, selective binding, and molecular recognition, aptamer-based hydrogels can be utilized for bioanalytical and biomedical applications. In this review, we focus on the latest strategies of aptamer-based hydrogels in bioanalytical and biomedical applications. We begin this review with an overview of the underlying design principles for the construction of aptamer-based hydrogels. Next, we will discuss some bioanalytical and biomedical applications of aptamer-based hydrogel including biosensing, target capture and release, logic devices, gene and cancer therapy. Finally, the recent progress of aptamer-based hydrogels is discussed, along with challenges and future perspectives.